Measurement of involute profile with small clamping eccentricity in a gear measuring center - Lianfu, Han (Strojniški vestnik, 2013)
This paper studies the influence of small clamping eccentricity on the measurement and evaluation of involute profile, analyzes the cause of clamping eccentric error, establishes a clamping eccentric error compensation model, and introduces a computing method of clamping eccentric parameters. Experimental testing of the computing method of clamping eccentric parameters proves that the computing method of clamping eccentric parameters is correct and feasible when the clamping eccentric value is within three quarters of the measurement range of the probe. The results of the clamping eccentricity error compensation experiment show that the clamping eccentric error compensation model can compensate measurement results to the results attained under operating conditions, and achieve precision measurement of involute profiles. The highest allowed clamping eccentric value can be extended to three quarters of the measurement range of the probe by the clamping eccentricity error compensation model proposed in this paper, thereby saving time otherwise spent adjusting for clamping eccentricity.
Keywords: analize; clamping eccentricity; ekscentričnost vpetja; evaluation; evolventni profil; gear measuring center; involute profile; measurement; meritve; preizkuševališče zobnikov